Confirmation and Identification of Salmonella spp., Cronobacter spp., and Other Gram-Negative Organisms by the Bruker MALDI Biotyper Method: Collaborative Study Method Extension to Include Campylobacter Species, Revised First Action 2017.09. (3rd December 2019) - Bastin, Benjamin; Bird, Patrick; Benzinger, M Joseph; Crowley, Erin; Agin, James; Goins, David; Sohier, Daniele; Timke, Markus; Shi, Gongyi; Kostrzewa, Markus
Abstract: Background: The Bruker MALDI Biotyper ® method utilizes matrix-assisted laser desorption/ionization time-of-flight MS for the rapid and accurate identification and confirmation of Gram-negative bacteria from select media types. The alternative method was evaluated in a method extension study of AOAC INTERNATIONAL First Action Official Method SM 2017.09 using nonselective and selective agars to identify Cronobacter spp., Salmonella spp., Campylobacter spp., and select Gram-negative bacteria. Results obtained by the Bruker MALDI Biotyper were compared to the traditional biochemical methods as prescribed in the appropriate reference methods. Methods: Two collaborative studies were organized, one in the United States focusing on Cronobacter spp. and other Gram-negative bacteria and one in Europe focusing on Salmonella spp. and other Gram-negative bacteria. Fourteen collaborators from seven laboratories located within the United States participated in the first collaborative study for Cronobacter spp. Fifteen collaborators from 15 service laboratories located within Europe participated in the second collaborative study for Salmonella spp. For each target organism (either Salmonella spp. or Cronobacter spp.), a total of 24 blind-coded isolates were evaluated. In each set of 24 organisms, there were 16 inclusivity organisms ( Cronobacter spp. or Salmonella spp.) and 8 exclusivity organisms (non- Cronobacter spp. and non- Salmonella spp. closely related Gram-negative organisms). For the Campylobacter spp. method extension, 17 collaborators from eight laboratories located within the United States (seven laboratories) and Canada (one laboratory) participated in the collaborative study. A total of 24 blind-coded isolates were evaluated. In each set of 24 organisms, there were 16 inclusivity organisms ( Campylobacter spp.) and 8 exclusivity organisms (non- Campylobacter spp. closely related Gram-negative organisms). Results: After testing was completed, the total percentage of correct identifications from each agar type for each strain was determined at a percentage of 100.0% to the genus level for the Cronobacter study and a percentage of 100.0% to the genus level for the Salmonella study. For the Campylobacter method extension, a correct identification and confirmation rate of 100.0% was obtained for the Campylobacter organisms at the species level. For non- Cronobacter, non- Salmonella, and non- Campylobacter organisms, 100.0% were correctly identified. Conclusions: The results indicated that the alternative method produced equivalent results when compared to the confirmatory procedures specified by each reference method. Highlights: The method extension can be modified to include the identification and confirmation of Campylobacter jejuni, Campylobacter coli, and Campylobacter lari .